Low Participation of Children's Weight as a Barrier to Acceleration Stunting Decrease in the Rural Area Bali Province: Further Analysis of Riskesdas 2018: Rendahnya Partisipasi Penimbangan Balita Sebagai Penghambat Percepatan Penurunan Stunting Di Wilayah Perdesaan Provinsi Bali: Analisis Lanjut Riskesdas 2018 - Hertog Nursanyoto; Anak Agung Ngurah Kusumajaya; Rofingatul Mubasyiroh; Sudikno; Olwin Nainggolan; Ni Ketut Sutiari; I Made Suarjana; Pande Putu Januraga; Kadek Tresna Adhi (Universitas Airlangga, 2023)
Stunting in rural areas tends to be higher than in urban areas. This study aims to determine the risk factors for stunting in rural areas in Bali. The analysis carried out is a further analysis of the 2018 basic health research (RISKESDAS 2018). The independent variable was the stunting status of children, which was determined based on the height-for-age index (HAZ). The independent variables consist of socio-demographic; the environment; and health services factors. The relationship between variables was analyzed by logistic regression method. Estimation of the proportion of stunting that can be prevented using Population Attributable Fraction (PAF) analysis. RISKESDAS 2018 data shows that the percentage of stunting in rural Bali is 29.3% higher than urban areas which is only 19.1%. The results of logistic regression analysis showed that under-fives weighing less than 8 times/year were at risk of stunting by 2.02 times compared to the other. PAF analysis shows that 3.5 percent of stunting under five in rural areas can be prevented by Monthly Weighing for children under five years old. Monthly Weighing in rural Bali through the Integrated Service Care (POSYANDU) is one of the efforts to prevent stunting children and monitor their the growth and development early.